Single-Molecule FISH Reveals Subcellular Localization of α-Amylase and Actin mRNAs in the Filamentous Fungus Aspergillus oryzae - Higuchi, Yujiro; Takegawa, Kaoru (Frontiers in Microbiology, 2020)
The machinery for mRNA localization is one of crucial molecular structures allowing cellular spatiotemporal organization of protein synthesis. Although the molecular mechanisms underlying mRNA localization have been thoroughly investigated in unicellular organisms, little is known about multicellular and multinuclear filamentous fungi. Here, we conducted single-molecule fluorescence in situ hybridization (smFISH) to first visualize the mRNA molecules of α-amylase, which are encoded by amyB, and which are thought to be abundantly secreted from the hyphal tips of the industrially important fungus Aspergillus oryzae. Consistent with previous biochemical studies, fluorescein amidite (FAM) fluorescence derived from amyB expression was observed in A. oryzae hyphae cultured in a minimal medium containing maltose instead of glucose as the sole carbon source. Moreover, after more than 1 h incubation with fresh maltose-containing medium, the fluorescence of amyB mRNAs was observed throughout the cells, suggesting α-amylase secretion potentially from each cell, instead of the hyphal tip only. Furthermore, in cultures with complete medium containing maltose, amyB mRNAs were excluded from the tip regions, where no nuclei exist. In contrast, mRNAs of actin, encoded by actA, were localized mainly to the tip, where actin proteins also preferentially reside. Collectively, our smFISH analyses revealed distinct localization patterns of α-amylase and actin mRNAs in A. oryzae hyphal cells.